The Role of Activated Stromal Cells in Fibrotic Foci Formation and Reversion - Nataliya Andreevna Basalova; Maksim Alexandrovich Vigovskiy; Vladimir Sergeevich Popov; Evgeniya Alexandrovna Lagereva; Olga Alexandrovna Grigorieva; Anastasia Yuryevna Efimenko (Cells)
Fibrotic focus is a pivotal morphofunctional unit in developing fibrosis in various tissues. For most fibrotic diseases, including progressive forms, the foci are considered unable to remodel and contribute to the worsening of prognosis. Unfortunately, the dynamics of the fibrotic focus formation and resolution remains understudied. A number of data suggest that the key cell type for focus formation are activated stromal cells marked by fibroblast activated protein alpha (FAPα) due to their high capacity for extracellular matrix (ECM) remodeling. We evaluated the dynamics of fibrotic focus formation and the contribution of the main cell types, including FAPα+ cells, in this process using a murine model of bleomycin-induced lung fibrosis. We revealed the very early appearance of FAPα+ cells in lungs after injury and assumed their important involvement to the myofibroblast pool formation. During the first month after bleomycin administration, FAPα+ cells colocalize with CD206+ M2 macrophages. Interestingly, during the reversion stage, we unexpectedly observed the specific structured foci formed by CD90+FAPα+ cells, which we suggested calling “remodeling foci”. Our findings highlight the crucial role of activated stromal cells in fibrosis initiation, progression, and reversion and provide emerging issues regarding the novel targets for antifibrotic therapy.